(untitled) (KYAMC Journal, 2018)
Malignant mesothelioma is one of the rare disease. It is an aggressive tumor arising from the mesothelial lining of the pleura or peritoneum. In our country there is no reported data or known incidence rate. It has an association with exposure to asbestos and usually has a poor prognosis. Early diagnosis and establishment of a standard treatment for malignant peritoneal mesothelioma is difficult. We report on a case of malignant peritoneal mesothelioma in a 59-year-old man with huge abdominal swelling, ascites and respiratory distress. KYAMC Journal Vol. 8, No.-2, Jan 2018, Page 40-42